Implementing PAIKEM Gembrot to Enhance Literacy, Numeracy, and Creativity in Elementary IPAS Learning - Agussalim Agussalim; W, Muhammad Fahreza; Radjab, Andi Mulyadi (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study investigates the implementation of the PAIKEM Gembrot model to enhance the literacy, numeracy, and creativity of fifth-grade students at UPT SDN Unjuruiya No. 45 in the Selayar Islands. Using a two-cycle classroom action research design—comprising planning, action, observation, and reflection—data were collected through tests, observations, and documentation to obtain comprehensive information on both learning processes and outcomes. In Cycle I, only 40% of students met the mastery criteria, largely due to their initial adjustment to the new learning approach and limited engagement in collaborative activities. After refining instructional strategies in Cycle II, including the use of more varied learning activities, concrete and contextual learning media, structured group discussions, and closer teacher guidance, student learning outcomes improved dramatically, with 100% of students achieving mastery. In addition, students showed increased participation, confidence, and motivation during classroom interactions. These results demonstrate that PAIKEM Gembrot effectively strengthens students’ abilities to comprehend information, apply numerical reasoning, and express creativity through active and meaningful learning experiences. Therefore, the PAIKEM Gembrot model serves as a promising and contextually relevant alternative for improving elementary science learning, particularly in island-based schools with limited educational resources.